Anthropometric profile and special judo fitness levels of Indian judo players - Katralli, J.; Goudar, S. S. (Asian Journal of Sports Medicine, 2012)
Purpose: Judo is a complex sport where different anthropological parameters determine performance. Judo, as a sport is not well known in India. There is evident lack of data concerning the anthropological determinants of judo players. This study was conducted to determine the anthropometric profile and special judo fitness levels of judokas.